The illusionist - Koppelman, Brian; Levien, David; London, Michael; Schulman, Cathy; Yari, Bob.; Burger, Neil.; Norton, Edward; Giamatti, Paul.; Biel, Jessica, 1982-; Sewell, Rufus, 1967-; Marsan, Eddie; Wood, Jake.; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
The acclaimed illusionist Eisenheim has not only captured the imaginations of all of Vienna, but also the interest of the ambitious Crown Prince Leopold. When Leopold's new fiancě rekindles a childhood fascination with Eisenheim, the Prince's interest evolves into obsession. Suddenly the city's Chief Inspector finds himself investigating a shocking crime. But even as the Inspector engages him in a dramatic challenge of wills, Eisenheim prepares for the most impressive illusion yet.
Title from container.
Based on the short story "Eisenheim, the illusionist" by Steven Millhauser.
Originally released as a motion picture in 2006.
Special features: Making-of 'The illusionist'; Jessica Biel on 'The illusionist'; trailer.
Director of photography, Pope, Dick ; editor, Naomi Geraghty ; music, Philip Glass ; costume designer, Ngila Dickson ; production designer, Ondrej Nekvasil.
Edward Norton, Paul Giamatti, Jessica Biel, Rufus Sewell, Eddie Marsan, Jake Wood, Tom Fisher.
Keywords: Magicians -- Austria -- Vienna -- Drama; Hallucinations and illusions -- Austria -- Vienna -- Drama; Magic tricks -- Austria -- Vienna -- Drama; Criminal behavior -- Austria -- Vienna -- Drama; Criminal investigation -- Austria -- Vienna -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Detective and mystery films